DINAMIKA KONFLIK TOKOH DALAM NOVEL KIDUNG RINDU DI TAPAL BATASKARYA AGUK IRAWAN MN KAJIAN PSIKOLOGI SASTRA - Sumadi Sumadi (EDU-KATA, 2020)
This study aims to describe (1) the form of conflict dynamics experienced by the figures and (2) the factors causing the conflict in Kidung Rindu novel in Tapal BatasAguk Irawan MN work. This research is a qualitative descriptive research using approach of Psychology Sastra.Data obtained by reading and record technique andanalyzed by qualitative descriptive analysis technique.The results of this study show: (1) There are two forms of conflict dynamics: internal and external conflicts, the five dominant ones include, anxiety over what has already happened, disagreements, fear of security threats, feelings of hurt, disappointment due to lack of attention, (2) Conflicting factors consisting of: trapped in complicated situations, discomfort with existing conditions, Differences in principles and mindset, reality is not in line with expectations, and the presence of new views. (3) The way to solve conflicts of characters includes, giving understanding, self-control, resignation to the circumstances, the search for truth, self-awareness,determination to makechanges, submitting to God.